2019
DOI: 10.1021/acscatal.9b02598
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Construction of 6,8-Dioxabicyclo[3.2.1]octane Frameworks from Vinylethylene Carbonates via Palladium-Organo Relay Catalysis

Abstract: The 6,8-dioxabicyclo­[3.2.1]­octane (6,8-DOBCO) architecture widely exists in a broad spectrum of bioactive natural products, and the development of efficient and convenient protocols to construct this skeleton remains a challenging task. Here, we report a concise synthetic strategy for the single-step construction of 6,8-DOBCO frameworks from simple vinylethylene carbonates and amine-substituted enones. This protocol features a sequential reaction of N-allylic substitution, Diels–Alder cyclization, and intram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…We envisioned that the design of a novel azaoxyallyl cation based on an oxindole skeleton might be quite interesting because the high reactivity of the azaoxylallyl cation intermediate could allow for rapid access to structurally challenging molecules, such as 3,3′-spiro­[β-lactam]-oxindoles. On the basis of these considerations and our continuous interest in assembling biologically relevant heterocycles, we herein report a highly diastereoselective [3 + 1] annulation of the newly designed oxindolyl azaoxyallyl cations with sulfur ylides. The present reaction could reach completion within a very short period of time, which further demonstrates the high reactivity of this new synthon.…”
mentioning
confidence: 99%
“…We envisioned that the design of a novel azaoxyallyl cation based on an oxindole skeleton might be quite interesting because the high reactivity of the azaoxylallyl cation intermediate could allow for rapid access to structurally challenging molecules, such as 3,3′-spiro­[β-lactam]-oxindoles. On the basis of these considerations and our continuous interest in assembling biologically relevant heterocycles, we herein report a highly diastereoselective [3 + 1] annulation of the newly designed oxindolyl azaoxyallyl cations with sulfur ylides. The present reaction could reach completion within a very short period of time, which further demonstrates the high reactivity of this new synthon.…”
mentioning
confidence: 99%
“…Based on our experimental results and by comparing to literature references, [8a,c,l] a plausible mechanism has been proposed in Scheme 3. The reaction is initiated via Pd‐catalyzed decarboxylation of VEC 1 a to give intermediate B , which undergoes a tautomeric process to generate cyclopalladated complex C as a key intermediate.…”
Section: Resultsmentioning
confidence: 52%
“…By using enones 82 tethered with a N ‐nucleophile as the reaction partners, a domino process including N ‐allylic substitution, intramolecular oxo‐Diels‐Alder reaction and ketalization were successfully realized, constructing a series of 6,8‐Dioxabicyclo[3.2.1]octane derivatives 85 in good yields (Scheme 44). [30b] Intermediates 83 and 84 were obtained through experimental verification, which demonstrated that the reaction was a palladium‐organo relay catalyzed domino process.…”
Section: π‐Allyl Palladium Bearing O‐nucleophilementioning
confidence: 94%